2019
DOI: 10.3960/jslrt.19021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis of multicentric and unicentric Castleman disease and TAFRO syndrome in Japan

Abstract: Castleman disease was initially described as a lymphoproliferative disorder causing mediastinal masses characterized by abnormal histopathology. 1 Castleman disease has since been subclassified clinically into unicentric (UCD) and multicentric Castleman disease (MCD), 2 and subclassified histopathologically into the hyaline-vascular type (HV), plasma-cell type (PC), mixed type, plasmablastic type, and hypervascular type. 3 MCD was recently subclassified into human herpes virus-8 (HHV-8)-associated, HHV-8unasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…Fifth, treatment strategies were not standardized; instead, they were chosen by attending physicians in each institute. However, because of the rarity of TAFRO syndrome [31], conducting a largescale prospective study on this syndrome is unrealistic at this moment, unfortunately.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, treatment strategies were not standardized; instead, they were chosen by attending physicians in each institute. However, because of the rarity of TAFRO syndrome [31], conducting a largescale prospective study on this syndrome is unrealistic at this moment, unfortunately.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to our knowledge to report incidence and prevalence estimates of CD and iMCD after the introduction of a CD-specific ICD-10 code and publication of international evidence-based diagnostic criteria for iMCD in 2017. 3 To date, data on the epidemiology of CD come from a variety of sources that include US academic centers, 12 Japan, 13 the Asia-Pacific region, 14 and US administrative claims databases. 3 Each of these studies reported on the incidence and prevalence of CD, UCD, and MCD, but not iMCD, primarily because of the lack of available criteria and specific disease code.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia, Anasarca, reticulin Fibrosis of the bone marrow, Renal dysfunction and organomegaly (TAFRO) syndrome is a very rare and severe variant of multicenter Castleman's disease firstly reported in Japan in 2010 1,2 . TAFRO syndrome is a hyper‐cytokine disease often caused by an uncontrolled HHV‐8 replication with a severe reduction of T follicular helper cells and atrophic lymphoid follicles; however, histology is not a mandatory diagnostic criterion for TAFRO 3 ; therefore, a prompt start of immunosuppressive and anti‐cytokine therapy is allowed.…”
Section: Updated Diagnostic Criteria Of Tafro Syndromementioning
confidence: 99%